Math, asked by JaipalBedre, 1 year ago

2(x + 3) = 8 - 3 (x - 4)​

Answers

Answered by Fifth
13

Answer:

x=2.8

Step-by-step explanation:

2(x+3) = 8-3(x-4)

2x + 6 = 8 - 3x + 12

2x + 3x = 8-6 + 12

5x = 14

x = 14/5 = 2.8

Answered by sayyadmohd78
2

Step-by-step explanation:

2x + 6 = 8 - 3x - 12

2x + 6 = -4 - 3x

2x + 6 + 4 = -3x

2x + 10 = - 3x

10 = -3x - 2x

10 = -5x

x = -5÷10

x = -1/2

If you are satisfy with my ans then mark me as a brainlist

if there is something wrong then kindly rectify it.

Similar questions